2011
DOI: 10.1088/0004-6256/141/3/73
|View full text |Cite
|
Sign up to set email alerts
|

DENSE CLUMPS IN GIANT MOLECULAR CLOUDS IN THE LARGE MAGELLANIC CLOUD: DENSITY AND TEMPERATURE DERIVED FROM13CO(J= 3-2) OBSERVATIONS

Abstract: In order to precisely determine the temperature and density of molecular gas in the Large Magellanic Cloud, we made observations of the optically thin 13 CO(J = 3-2) transition using the ASTE 10 m telescope toward nine peaks where 12 CO(J = 3-2) clumps were previously detected with the same telescope. The molecular clumps include those in giant molecular cloud (GMC) Types I (with no signs of massive star formation), II (with H ii regions only), and III (with H ii regions and young star clusters). We detected 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 49 publications
(83 reference statements)
4
50
0
Order By: Relevance
“…3, this condition is only valid for kinetic temperatures higher than 120 K for a volume density range between 3 × 10 3 −10 4 cm −3 . The intersection of the two CO line ratios constrains the CO column density per velocity interval to about 3 × 10 17 cm −2 /km s −1 at T kin 160 K. The derived kinetic temperature and H 2 density are consistent with previously published excitation analyzes based on CO observations Kim 2006;Minamidani et al 2008Minamidani et al , 2011. Figure 4 shows that the model-predicted clump-averaged absolute line intensity of the 13 CO J = 4 → 3 line, at the column 1 For an example of a typical temperature distribution and abundance structure of the main carbon species in PDRs, see e.g.…”
Section: Co-emissionsupporting
confidence: 89%
“…3, this condition is only valid for kinetic temperatures higher than 120 K for a volume density range between 3 × 10 3 −10 4 cm −3 . The intersection of the two CO line ratios constrains the CO column density per velocity interval to about 3 × 10 17 cm −2 /km s −1 at T kin 160 K. The derived kinetic temperature and H 2 density are consistent with previously published excitation analyzes based on CO observations Kim 2006;Minamidani et al 2008Minamidani et al , 2011. Figure 4 shows that the model-predicted clump-averaged absolute line intensity of the 13 CO J = 4 → 3 line, at the column 1 For an example of a typical temperature distribution and abundance structure of the main carbon species in PDRs, see e.g.…”
Section: Co-emissionsupporting
confidence: 89%
“…The critical densities of CO(3-2) and CO(6-5) are (3-4)×10 4 cm −3 and 3 × 10 5 cm −3 , respectively, for 10-100 K (calculated using Flower 2001; Goorvitch 1994). Minamidani et al (2011) derived n(H 2 ) of (4-5)×10 3 cm −3 for N159 W and E, and Pineda et al (2008) discuss the result of PDR modeling with an average density of the clump ensemble of about 10 5 cm −3 . These densities are consistent with the assumption that the CO(6-5) emission does not reach LTE, in contrast to with the RADEX radiative transfer program show that the CO(3-2)/CO(6-5) intensity ratio at 30-100 K changes by more than a factor of 2 between 10 4 -10 5 cm −3 (van der Tak et al 2007), which can explain the CO(6-5) discrepancy in Fig.…”
Section: Column Densities Of C + C and Comentioning
confidence: 99%
“…When we estimate T ex at N159 W and E in the same spatial resolution, η = 0.3-0.4 gives the same temperature for T ex as their dust temperature. Minamidani et al (2011) derive the kinetic temperature from a LVG analysis with 45 ′′ resolution to be 40-82 K and 65-151 K in N159 W and E, respectively. If we assume that T ex equals their kinetic temperature, it requires a value for η of < 0.3.…”
Section: Column Densities Of C + C and Comentioning
confidence: 99%
“…We use the CO J = 1-0 transition observed References. (a) SAGE (Meixner et al 2006); (b) HERITAGE (Meixner et al 2013) with Mopra (Wong et al 2011) and CO J = 3-2 observed with the Atacama Submillimeter Telescope Experiment (ASTE; Minamidani et al 2011;see Fig. 2).…”
Section: Ground-based Observationsmentioning
confidence: 99%